The correlation between peripheral complete blood count parameters and diabetic macular edema in proliferative diabetic retinopathy patients: a cross-sectional study - Lei, Chunyan; Gu, Jinyue; Liu, Lili; Zhang, Keren; Zhang, Meixia (Frontiers in Endocrinology, 2023)
Background Numerous studies have demonstrated that retinal chronic inflammation plays a critical role in the pathogenesis of diabetic macular edema (DME). However, studies about the association between peripheral complete blood count, an inexpensive and easily measurable laboratory index, and DME are limited. Research design and methods The current study was a hospital-based, cross-sectional study. The participants were inpatients with type 2 diabetes who underwent vitrectomy for PDR, and the contralateral eyes in these PDR patients meeting the criteria were included in the study. Central macular thickness (CMT) was measured automatically and the DME was characterized as CMT ≥ 300 μm. Results A total of 239 PDR participants were enrolled. The average age was 55.46 ± 10.08 years old, and the average CMT was 284.23 ± 122.09 μm. In the fully adjusted model, for CMT, the results revealed a significantly negative association between CMT and both white blood cell (WBC) count and neutrophil count (β = −11.95, 95% CI: −22.08, −1.82; p = 0.0218; β = −14.96, 95% CI: −28.02, −1.90; p = 0.0259, respectively); for DME, the results showed an inverse association between DME and WBC count, monocyte count, and eosinophil count (OR = 0.75, 95% CI: 0.59, 0.95; p = 0.0153; OR = 0.07, 95% CI: 0.00, 0.92; p = 0.0431; OR = 0.03, 95% CI: 0.00, 0.88; p = 0.0420, respectively). Conclusions In conclusion, our results suggest that WBC and its subtypes in circulation may play an important role in the pathogenesis of DME in PDR patients.